2015
DOI: 10.1080/09168451.2014.998621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Avt1p as a vacuolar proton/amino acid antiporter in Saccharomyces cerevisiae

Abstract: Several genes for vacuolar amino acid transport were reported in Saccharomyces cerevisiae, but have not well been investigated. We characterized AVT1, a member of the AVT vacuolar transporter family, which is reported to be involved in lifespan of yeast. ATP-dependent uptake of isoleucine and histidine by the vacuolar vesicles of an AVT exporter mutant was lost by introducing avt1∆ mutation. Uptake activity was inhibited by the V-ATPase inhibitor: concanamycin A and a protonophore. Isoleucine uptake was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 33 publications
0
31
1
Order By: Relevance
“…A recent report on the extension of replicative lifespan via Avt1 (Hughes and Gottschling, 2012) was shown to spotlight a general significance of vacuolar amino acid uptake. Although previous reports have not detected the in vitro ATPdependent import activity at the vacuolar membrane (Ohsumi and Anraku, 1981;Sato et al, 1984;Tone et al, 2015b), our results showed that proline is significantly accumulated in the vacuole in vivo at least in the presence of exogenous proline (Fig. 4).…”
Section: Fig 4 Cytosolic and Vacuolar Amino Acid Contents Of Straincontrasting
confidence: 76%
See 3 more Smart Citations
“…A recent report on the extension of replicative lifespan via Avt1 (Hughes and Gottschling, 2012) was shown to spotlight a general significance of vacuolar amino acid uptake. Although previous reports have not detected the in vitro ATPdependent import activity at the vacuolar membrane (Ohsumi and Anraku, 1981;Sato et al, 1984;Tone et al, 2015b), our results showed that proline is significantly accumulated in the vacuole in vivo at least in the presence of exogenous proline (Fig. 4).…”
Section: Fig 4 Cytosolic and Vacuolar Amino Acid Contents Of Straincontrasting
confidence: 76%
“…5 and 6), as well as of other large neutral amino acids, such as glutamine, asparagine, leucine, isoleucine, and tyrosine (Russnak et al, 2001;Tone et al, 2015b). We previously reported that the vacuolar function is essential for maintaining cell viability under stress conditions in a prolineaccumulating mutant (Matsuura and Takagi, 2005).…”
Section: Fig 4 Cytosolic and Vacuolar Amino Acid Contents Of Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…14) Uptake of arginine was assayed as described. 29) Vacuolar membrane vesicles (200 μg of protein) were incubated for 5 min at 25°C in the assay mixture (500 μL) consisting of 25 mM MES-Tris (pH 7.0), 4 mM MgCl 2 , and 25 mM KCl. ATP (2 mM) was added to the mixture and incubated for 1 min at 25°C.…”
Section: Plasmid Constructionmentioning
confidence: 99%